Perkembangan dan Tren Penelitian Pengungkapan Anti-Korupsi: Sebuah Tinjauan Literatur Empiris - Avia Tamara Shabirina; Ibrahim Fatwa Wijaya (Politeknik Ganesha Medan, 2026)
This study employs a Systematic Literature Review (SLR) using the PRISMA framework to examine the development of anti-corruption disclosure research. A total of 45 Scopus-indexed articles published between 2015 and 2026 were systematically analyzed. The findings indicate that anti-corruption disclosure not only serves as a transparency mechanism but also functions as a strategic instrument to strengthen corporate governance, mitigate fraud and corruption risks, and enhance stakeholder trust and corporate reputation. Three main themes emerge from the review: (1) the role of disclosure in reinforcing governance mechanisms and accountability, (2) its function in mitigating fraud and corruption through increased monitoring and control, and (3) its contribution to building legitimacy and stakeholder trust. However, the review also identifies several challenges, including the use of procedural disclosure measures that do not fully capture substantive practices, methodological weaknesses related to potential bias and causality issues, and sample heterogeneity that may affect the validity of findings. Overall, this study contributes by providing a comprehensive synthesis of the literature and offering implications for future research and corporate practices oriented toward integrity and sustainability.